(untitled) (Journal of actual problems of jurisprudence, 2018)
This report reveals the state of Kazakhstan’s jurisprudence, identifies problems, outlines development prospects, suggests recommendations. The conclusion is made that legal science should determine strategic directions for further improvement of all branches of national law, law enforcement and judicial systems, as well as legal bases for foreign policy and foreign economic activity. The report gives a general description of the Kazakhstani legal science. It is emphasized that the legal science is closely connected with the legal education. In this area, there are many problems. It was concluded that the reforms carried out in the educational system in accordance with the Bologna Convention (Bologna process) in the training of scientific personnel did not bring the expected positive results. Current trends in the development of the legal science of Kazakhstan in the field of civil law, administrative law, juvenile law, environmental law are outlined. The report emphasizes that the availability of scientific personnel in universities and institutes is low. The prestige of the scientists is not high. There is no interest of young people to engage in scientific research. It is necessary to stimulate the inflow of fresh personnel into science.. The following suggestions on the development of the legal science of Kazakhstan were made in the report. It is proposed to expand the list of journals recommended by the Ministry of Education and Science of the Republic of Kazakhstan for publication of the results of doctoral studies. It is suggested that the RINC be transferred to the «Law» section under the jurisdiction of the al-Farabi Kazakh National University. It is proposed to increase the number of PhD grants in the law sciences by 2-3 times to prepare doctoral students. It is recommended to reduce the theoretical training of doctoral students (PhD) to two semesters of the first year. It is recommended to create a Kazakhstani science-based system based on the NGTSTI with the appropriate personnel and technical support in the RINC model. It is recommended to establish medals and prizes named after prominent scientists for young lawyers. Key words. Legal science, legal education, law, doctoral studies, academic lawyers, Bologna process.